2009
DOI: 10.1111/j.1462-2920.2008.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

A genomic island of the sulfate‐reducing bacterium Desulfovibrio vulgaris Hildenborough promotes survival under stress conditions while decreasing the efficiency of anaerobic growth

Abstract: A 47 kb genomic island (GEI) bracketed by 50 bp direct repeats, containing 52 annotated genes, was found to delete spontaneously from the genome of Desulfovibrio vulgaris Hildenborough. The island contains genes for site-specific recombinases and transposases, rubredoxin:oxygen oxidoreductase-1 (Roo1) and hybrid cluster protein-1 (Hcp1), which promote survival in air and nitrite stress. The numbering distinguishes these from the Roo2 and Hcp2 homologues for which the genes are located elsewhere in the genome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…However, the incomplete recovery of the mutant strains observed upon inhibition of iNOS suggests that they also participate in protection against other stresses, such as oxidative stress, imposed by the macrophages. Studies in oxygenated environments showing that the roo and hcp mutations decrease D. vulgaris survival under conditions of oxidative stress corroborate this hypothesis (18,24,27,28,39).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, the incomplete recovery of the mutant strains observed upon inhibition of iNOS suggests that they also participate in protection against other stresses, such as oxidative stress, imposed by the macrophages. Studies in oxygenated environments showing that the roo and hcp mutations decrease D. vulgaris survival under conditions of oxidative stress corroborate this hypothesis (18,24,27,28,39).…”
Section: Discussionsupporting
confidence: 62%
“…with known genome sequences, D. vulgaris Hildenborough contains two homologues of the FDPs (ROO1 and ROO2) and of HCPs (HCP1 and HCP2). The genes encoding ROO1 (DVU2014) and HCP1 (DVU2013) are adjacent within a genomic island (24), while the genes encoding ROO2 (DVU3185) and HCP2 (DVU2543) are located elsewhere and are separated in the genome. In Desulfovibrio spp., these proteins are proposed to promote survival in oxygenated environments and to remove RNS generated by nitrite reduction (24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…However, there were no significant changes in EhFdp1 transcript abundance under a variety of conditions, including response to NO-derived stress (1, 2, 11, 13, 42). FDPs have been shown to be highly and constitutively expressed both in prokaryotes (in some cases incorporating an oxidative stress response operon [8,18]) and in protozoa (10,25,32). However, an increase in expression upon oxygen exposure has been observed for only one other FDP, that from the hyperthermophilic bacterium Thermotoga maritima, which shows an increase in protein levels with unmatched transcriptional levels and is proposed to sustain the growth of this "strict" anaerobe under microaerophilic conditions (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…These include DVU3183 superoxide reductase (sor), as well as the NADH peroxidases DVU3094 rubrerythrin-1 (rbr1), DVU2310 rubrerythrin-2 (rbr2) and DVU0019 nigerythrin (ngr). D. vulgaris also removes oxygen by protective respiration using membrane-bound oxygen reductases Cox (DVU1811-1815) and Cyd (DVU3270-3271), as well as the cytoplasmic rubredoxin:oxygen oxidoreductases DVU2014 Roo1 and DVU3185 Roo2 (Frazão et al 2000;Johnston et al 2009;Lemos et al 2001;Lobo et al 2008). Deletion analysis has indicated that Roo1 and Roo2 confer resistance to oxygen-mediated killing under microaerophilic conditions, whereas Sor protects against killing under fully aerobic conditions (Johnston et al 2009;Wildschut et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The effect of oxygen-and H 2 O 2 -stress on geneexpression in D. vulgaris has been studied extensively (Brioukhanov et al 2010;Johnston et al 2009;Mukhopadhyay et al 2007;Pereira et. al.…”
Section: Introductionmentioning
confidence: 99%